Gestão da Informação e do Conhecimento em redes sociais virtuais: proposição de um modelo explicativo para busca de informação e geração de conhecimento para lidar com o autismo - Leandro Cearenço Lima (2024)
In recent years, discussions about knowledge in physical and/or virtual channels have been gaining strength in the scientific community. Object of reflection and study in several areas, especially due to the recognition that human beings achieve greater success as a species through a process of cooperation, digital platforms have been gaining prominence and represent ideal enabling context environments for exploring phenomena. Given this context, this thesis aims to propose a model, a representation of reality, that highlights the stages (moments) passed by parents of autistic children on the social network Facebook to seek information and generate knowledge to deal with Autism Spectrum Disorder – ASD.This model aims to propose a description of how the individual's journey happens from the information and knowledge gap to obtaining new knowledge or good practices to deal with the context of autism in the family. The methodology for operationalizing the research included a qualitative approach based on a systematic literature review, in addition to semi-structured interviews to expand the understanding of the research object and logical construction of the model. Data extraction and analysis tools were also used, such as Word Clouds.com, which allowed categorizing and highlighting the most relevant data, the Meta Insights software, which allowed data capture directly from the Facebook platform, as well as Microsoft Excel , to organize, tabulate and combine data. Using content analysis techniques, the collected and organized data were related to the contexts of families with individuals on the autism spectrum, allowing empirical testing of the model. The results indicated the validity of the model proposed on the Facebook platform in a thematic group for mothers of autistic people. It can be concluded that the importance of the model's contribution to society has been demonstrated, as it theoretically describes the journey of individuals to obtain knowledge, good practices and support to deal with a disorder that afflicts a large number of families. It is also worth highlighting the contributions of this research to science, as validating the model as a tool for explaining a phenomenon allows it to be replicated and tested in other contexts, environments and platforms in different areas of knowledge. As a gap, it is clear that the literature still needs to expand the number of studies that address Knowledge Management issues and that involve the Enabling Context. Finally, it is hoped that this research effort will advance from future studies and can serve as support for other researchers and teachers in their areas, as well as for parents of autistic people and society to expand knowledge about the context addressed.